2009
DOI: 10.1016/j.applthermaleng.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Single-phase heat transfer in microchannels: The importance of scaling effects

Abstract: Microscale single-phase heat transfer is widely used in industrial and scientific applications and for this reason, many related papers have been published in the last two decades. Nevertheless, inconsistencies between published results still exist and there is no generally accepted model for the prediction of singlephase heat transfer in microchannels. This paper presents a review of the experimental and numerical results available in the open literature. Heat transfer in microchannels can be suitably describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(132 citation statements)
references
References 62 publications
4
117
0
1
Order By: Relevance
“…Particularly, Figure 5 shows the velocity and temperature contours in the cross-section of the Microchannels 1 and 3 4 for z* ≅ 0.36, in the flow with Re = 200. Figures 5(a-b) show the velocity contours for the Microchannels 1 and 3, respectively, whereas Figures 5(c-d) show the temperature contours for the Microchannels 1 and 3, respectively.…”
Section: Velocity and Temperature Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, Figure 5 shows the velocity and temperature contours in the cross-section of the Microchannels 1 and 3 4 for z* ≅ 0.36, in the flow with Re = 200. Figures 5(a-b) show the velocity contours for the Microchannels 1 and 3, respectively, whereas Figures 5(c-d) show the temperature contours for the Microchannels 1 and 3, respectively.…”
Section: Velocity and Temperature Profilesmentioning
confidence: 99%
“…At the same time, this reduction in physical space is counterweighted by the high performance required at the refrigeration systems in such equipment. Therefore, thermal control is one of the most critical areas for the development of modern microelectronic devices [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, heat transfer in micro-channels has been extensively studied, however, published results are still inconsistent; some studies have found the average Nusselt number to be Reynolds number dependent in the laminar regime [10][11][12], some recorded lower Nusselt numbers [13][14][15] while some recorded higher Nusselt numbers [16][17][18]. Reviews on experimental and numerical studies of heat transfer in microchannels published by Mokrani, Bourouga, Castelain and Peerhossaini [19], Hetsroni, Mosyak, Pogrebnyak and Yarin [20], Rosa, Karayiannis and Collins [21] and Sobhan and Garimella [22] confirm the very large scatter in published results and attribute this to "scaling effects", which arise from neglecting phenomenon which are insignificant in conventional sized channels but become significant with the high channel wall surface to fluid volume ratio in microchannel flow. Some examples of these include surface roughness [14], entrance and exit effects [23,24], axial conduction effects [15,25], thermal boundary conditions [26], viscous dissipation effects [27], electric double layer [28] and increased measurement uncertainties [29].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Bayazitoglu et al [6], Rosa et al [7], Cetin et al [8], Cetin [9], Haddout and Lahjomri [10] and Yu and Ameel [11] observed that velocity slip increases the Nusselt number (Nu ÂŒ (h  D H )/k, where h is convective and k is the conductive heat transfer coefficients of fluid), while the temperature jump has a negative effect on heat transfer in single phase microchannel flows.…”
Section: Introductionmentioning
confidence: 99%